Evaluation review of the 250Cf neutron cross section. (December 2019) - Alrwashdeh, Mohammad; Alameri, Saeed
Abstract: This research investigated the data for the cross section of the 250 Cf isotope in the unresolved resonance region, where the incident particle with a specific energy is either neutral or charged. Both the angular distribution and the differential cross sections of 250 Cf were evaluated in the specific energy range. In this research, the Reich-Moore R-matrix approximation was used to evaluate the theoretical cross section, and sophisticated models were employed to evaluate and describe the background experimental data by including the reduction parameters for the experimental data. The evaluated resonance integral-capture cross section and thermal resonance integral-capture cross section showed a good agreement with the tabulated values found in the literature on the unresolved resonance energy region for 250 Cf in the range from 0.01 meV to 20 meV. Highlights: This research investigated the data for the cross section of the 250 Cf isotope in the unresolved resonance region, where the incident particle with a specific energy is either neutral or charged. Thermal benchmark evaluation for the Maxwellian-averaged cross sections of total, capture, and fission reactions along with the Wescott factors. The present reseach is enchancing the important quantities in order to do more benchmark in near future.